Masalah Dan Strategi Koping Penyintas Covid - Srimiyati; Betty Elisabet Gultom; Ketut Suryani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Background: a pandemic has hit the whole world, including Indonesia, the current pandemic is covid-19. Covid-19 is a virus caused by the SARS coronavirus (SARS CoV-2). The Covid-19 virus is pread through the saliva of person who is positive for covid-19. Due to the easy spread process, many people are infected with the virus, causing death. Threre are many expriences by sameone infected with the Covid-19 virus, ranging from psysical, psychological and economic complaints. One of the complaints often experiences is the fear of dying when infected with this virus. Objective: This study aims to analyze and dig deeper into a person's experience regarding the problems and strategies of Covid-19 survivor. Method: The research method that the researcher uses is qualitative using a phenomenological approach. The data collection process was carried out by means of interviews/indept interviews using interview guidelines. The process of sampling technique used is purposive sampling. The research process that has been carried out has obtained 5 participants who have declared data saturation. The results of the study: based on the results of the research that the researchers had conducted, three themes were found as follows: 1) Constraints experienced by survivors while suffering from covid-19, 2) health problems experienced after recovering from covid-19, 3) efforts made by survivors.